Menara Celcom, Kuala Lumpur / Muhammad Lutfil Hadi Osman ... [et al.] - Osman, Muhammad Lutfil Hadi; Zalizan, Afiq Farhan; Roslan, Mohd Fathulnaim Hazim; Onn, Fariha Ilyany; Mohd Nazari, Hana Syahira (Universiti Teknologi Mara, Perak, 2017)
The purpose of this Final Project BSR (330) is to make sure that we are apply what have been learn from 1st semester until 5th semester. It was compulsory for us Building Survey students to carry out this report because it must need to compile the requirement and task before we are been graduate. By doing this project, we are required to knows about all information of Menara Celcom building from the substructure until super structure. The case study that we have been chosen are Menara Celcom Jalan Raja Muda Abdul Aziz located at the end of Jalan Semarak, Kuala Lumpur. Menara Celcom is strategically located on the front building have a Pusat Perubatan Homeopathy Zuhaimi there is located at business building. Then on the right of the building have a Perodua service centre at Jalan Gurney and on the left have a office building it’s call Wisma Perkeso located at Jalan Tun Razak. Finally, at the back of the building it’s call Menara Marinara is located at in front the Jalan Tun Razak. The Menara Celcom has a good view. It has fully covered with glass and the shape of the rear view this building is quite similar to the shape of a broadband which symbolizes their main business. Menara Celcom is full covered by glass. It is good to reduce a lot of using light in the building, it get direct sunlight during daytime. The Menara Celcom has 24 level and 5 basement. Starting from floor basement 5 until basement 1the floor they were used as the carpark. Then starting from level 1 until 22 is been rent to Celcom (Malaysia) Sdn.Bhd. for the owner of the building they only use 124 016 sqf for their office level at level 2 a rest it been rent to TMR Urusharta (M) Sdn.Bhd, MyNews, KLinik Zarif and Celcom Gymnasium. As the conclusion by doing this Final Project we gain more information and knowledge about the maintenance work, safety of the building and many more. We are glad because from this project we have knew everything on how to solve problem, how to work with professional workers and many more. We hope that, the report which has been done by our group in followed the requirement that need and give satisfactions by the lecturer.